Analisis Kesiapan Guru dalam Merencanakan Pembelajaran Intrakurikuler pada Kurikulum Merdeka di Kelas II dan V MI Al Hidayah - Ummah, Kholifatul; Fajrin, Nilamsari Damayanti (Yayasan Arrahman Nahdlatul Wathan, 2024)
Readiness is a condition where a person is ready both physically, mentally and mentally to carry out an activity. In this readiness, there are several teacher readiness in planning intracurricular learning in the independent curriculum. The aim of this research is to determine teacher readiness in planning intracurricular learning in the independent curriculum in classes II and V at MI Al Hidayah. This research uses a descriptive qualitative approach. In this study, the research subjects were the teachers of MI Al Hidayah, involving 8 informants, namely 2 male teachers and 6 female teachers. Data collection techniques in this research are interviews and documentation. The data validity technique used by researchers is source triangulation. The results of the analysis show that the readiness of class II and V MI Al Hidayah teachers in terms of understanding CP says that the existing CP is in accordance with the character of students, in terms of formulating TP teachers have several steps in formulating TP, in preparing ATP there are things that teachers must pay attention to. in its preparation. Class II and V MI Al Hidayah teachers are given freedom in planning this lesson, but the dominant teacher chooses the teaching module. Class II and V teachers and other teachers involved have prepared various intracurricular learning plans for the independent curriculum in classes II and V at MI Al Hidayah.